The Corporate Governance Mechanisms in ASEAN Context: A Literature Review - Endah Susilowati; Corina Joseph; Vicky Vendy; Indrawati Yuhertiana; Alfi Ardiyanti; Ananda Faticha Putri (Future Science, 2022)
This study aims to review the prior studies regarding the corporate governance mechanisms in ASEAN countries. This study uses 11 selected articles published in 2018-2022 in the Scopus journal database. This study found that corporate governance mechanisms can have an impact on bank efficiency, Non-Discretionary Profits, disclosure quality, audit quality, investor reaction, tax avoidance, cost of capital, and financial distress. Further studies are encouraged by including more journal databases to gather more relevant literature in discussing corporate governance in the context of ASEAN countries.